Gender and Career Progression in Academia: European Evidence - Lucio Morettini; Massimiliano Tani (Institute of Labor Economics (IZA), 2023)
We study career trajectories of university researchers in Europe, with a particular emphasis on the speed of career progression by gender. Using the panel data collected by the MORE project (Mobility Survey of the Higher Education Sector) - a longitudinal database that gathers survey responses from over 10,000 university researchers across Europe - we find that women have a lower probability of promotion, but conditional on a career advance, their career development proceeds at a faster pace than that of comparable male researchers. Faster progression among women is positively influenced by the share of female researchers in the academic environment. Higher salaries in sectors outside academia appear to reinforce the positive selection of women preferring to stay in academia.
Keywords: J20; J24; J62; 330; academic careers; career progression; promotion